Interaction of multimicrobial synthetic inhibitor 1,2-bis(2-benzimidazolyl)-1,2-ethanediol with serum albumin: spectroscopic and computational studies. - Nayana Kamtekar; Anita Pandey; Neeraj Agrawal; Raghuvir R S Pissurlenkar; Mohanish Borana; Basir Ahmad (PLoS ONE, 2013)
The molecule, 1,2-Bis(2-benzimidazolyl)-1,2-ethanediol (BBE) is known to act as a selective inhibitor of poliovirus, rhinovirus, Candida albicans, several bacterial species, and is easily synthesized by Phillips reaction. The interaction of BBE with BSA and the effects of its binding on the conformation and unfolding/refolding pathways of the protein were investigated using multispectroscopic techniques and molecular modeling. The binding studies indicate that BSA has one high affinity BBE binding site with association constant 6.02±0.05×10(4) M(-1) at 298 K. By measuring binding at different temperatures, we determined the changes in enthalpy (ΔH = -15.13±2.15 kJ mol(-1)), entropy (ΔS = 40.87±7.25 J mol(-1) K(-1)) and free energy (ΔG( = )26.78±1.02) of interaction, which indicate that the binding was spontaneous and both enthalpically and entropically driven. Based on molecular modeling and thermodynamic parameters, we proposed that the complex formation involved mainly hydrophilic interaction such as hydrogen bonding between hydroxyl groups of ethane-1,2-diol fragment with Tyr410 and benzimidazole sp(2) nitrogen atom with Ser488 and hydrophobic interaction between phenyl ring of one benzimidazole of the ligand and hydrophobic residues namely, Ile387, Cys391, Phe402, Val432 and Cys437. The sequential unfolding mechanism of BSA, site-specific marker displacement experiments and molecular modeling showed that the molecule preferably binds in subdomain IIIA. The BBE binding to BSA was found to cause both secondary and tertiary structural alterations in the protein as studied by intrinsic fluorescence, near-UV and far-UV circular dichroism results. The unfolding/refolding study showed that BBE stabilized native to intermediate states (N⇌I) transition of the protein by ∼2 kJ mol(-1) without affecting the intermediate to unfolded states (I⇌U) transition and general mechanism of unfolding of BSA.